O escape existe? o paradoxo do escapismo na pesquisa do comportamento do consumidor - Sousa , Thamiris Magalhães de (2024)
Although there is a wide range of studies on escapism in consumer behavior research, the complexity of this process, which gives rise to its paradox, has often been ignored in the existing literature. Escapism has been treated as an escape from reality, without making this process complex. In other words, the escape ends up being a momentary escape from reality. However, what is clear and what this study seeks to contribute to is that, even in a moment of escape, there may be self-awareness complicating this process. Therefore, current research aims to make significant contributions by addressing these research gaps by demonstrating and investigating the complexity and paradox of escapism. First, it advances the literature, providing a holistic view of escapism, as well as the evolution of the concept of escape over the years, evaluating how escapism has been studied in consumer behavior research, which offers visions of the future, suggestions for new seminal research and works, as well as research gaps and topics that are still little addressed in the area, such as the escape paradox. Secondly, the research addresses the paradox of escapism in consumer research, in a research that approaches in a preliminary and innovative way the constructs that encompass escape and its paradox, its developments and intersections with escapism, as well as analyzing the pitfalls of escape, which lead to paradox. The research proposition is that the paradox of escapism is an unfolding and an evolution of the concept of escapism. Subsequently, the measurement of the paradox of escapism is validated through a survey with 521 individuals. This thesis contributes to the consolidation and improvement of the escapist consumer theory, as well as the Consumer Culture Theory (CCT), as it identifies a set of characteristics of behaviors considered paradoxical, which represents an innovation in the consumer behavior literature and escapism. Overall, the research provides a valid contribution of the paradox of escapism in people's lives.